2008
DOI: 10.1634/stemcells.2008-0506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stem Cells During Prepubertal Spermatogenesis via Monitoring of Nucleostemin Promoter Activity

Abstract: The nucleostemin (NS) gene encodes a nucleolar protein found at high levels in several types of stem cells and tumor cell lines. The function of NS is unclear but it may play a critical role in S-phase entry by stem/progenitor cells. Here we characterize NS expression in murine male germ cells. Although NS protein was highly expressed in the nucleoli of all primordial germ cells, only a limited number of gonocytes showed NS expression in neonatal testes. In adult testes, NS protein was expressed at high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…This finding corroborates previous studies indicating that prespermatogenic germ cells are a heterogeneous population differing not only in their localization in seminiferous epithelium and morphology but also in their expression of specific molecular markers such as transcription factor OCT-4, tyrosine kinase receptor c-KIT and Melanoma antigen-A4 (MAGE-A4) (Fukuda et al, 1975;Gaskell et al, 2004;Yoshida et al, 2006;Ohmura et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates previous studies indicating that prespermatogenic germ cells are a heterogeneous population differing not only in their localization in seminiferous epithelium and morphology but also in their expression of specific molecular markers such as transcription factor OCT-4, tyrosine kinase receptor c-KIT and Melanoma antigen-A4 (MAGE-A4) (Fukuda et al, 1975;Gaskell et al, 2004;Yoshida et al, 2006;Ohmura et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Ohumura and colleagues recently showed that a nucleolar protein called nucleostemin, found at high levels in several types of stem cells, identifies germ cells with undifferentiated status and long-term testis repopulating capability in prenatal gonads (Ohmura et al, 2008). Interestingly, the expression pattern of this protein closely resembles that of the SP phenotype described here.…”
Section: Resultssupporting
confidence: 69%
“…A previous study indicated that, in the adult testis, the SP fraction also contains stem/progenitors for androgen-producing Leydig cells in addition to SSCs (Lo et al, 2004). It would be interesting to test whether embryonic Leydig progenitor cells are also present in the SP fraction from prenatal testes.Ohumura and colleagues recently showed that a nucleolar protein called nucleostemin, found at high levels in several types of stem cells, identifies germ cells with undifferentiated status and long-term testis repopulating capability in prenatal gonads (Ohmura et al, 2008). Interestingly, the expression pattern of this protein closely resembles that of the SP phenotype described here.…”
supporting
confidence: 69%
“…Nucleostemin was discovered because of its high expression in neuroepithelial stem or progenitor cells purified from the fetal forebrain (Tsai and McKay, 2002) and was later found to be highly expressed in other types of stem cells, tumors, and tumorinitiating cells or cancer stem cells (CSCs) (Baddoo et al, 2003;Lin et al, 2010;Ohmura et al, 2008;Tamase et al, 2009;Tsai and McKay, 2002;Yamashita et al, 2013). By contrast, in differentiated cells and tissues, this protein is expressed at a much lower level, except for those undergoing regeneration Maki et al, 2007;Shugo et al, 2012;Siddiqi et al, 2008).…”
Section: History and Mysteriesmentioning
confidence: 99%